Investment strategies for different actors in indoor mobile market: "In view of the emerging spectrum authorization schemes" - Ashraf Awadelakrim Widaa; Jan Markendahl; Amirhossein Ghanbari (International Telecommunications Society (ITS), 2013)
The regulatory landscape is changing towards more flexible spectrum management schemes. Such schemes are expected to make additional spectrum resources available and lower the spectrum access barriers. Emerging spectrum authorization schemes such as secondary access (TV White Space) and Licensed Shared Access (LSA) are expected to open doors for new actors rather than traditional MNOs to access licensed spectrum resources at reasonable costs. These schemes will allow actors such as Facility Owners (FO), Mobile Virtual Network Operators (MVNO) and Internet Service Providers (ISPs) to invest in indoor mobile network infrastructure. These actors can act as Local Network Operators (LNO) and build their business models around provisioning of mobile services in locations where there seems to be a hole or lack of service coverage in a particular area within the mobile network operators (MNOs) service footprint. This paper highlights the differences between indoor deployment and outdoor deployment in the light of the available spectrum bands to be used and the possible business models for MNOs and LNOs. In short, the possible investment strategies for provisioning indoor mobile services vary between MNOs and LNOs cases due to economic and regulatory aspects surrounding them. The main finding in this study indicates that the willingness of MNOs to invest in dedicated indoor solutions is driven by the balance between the potential revenues and the deployment cost. Moreover MNOs have more spectrum and investment options compared to LNOs who must bond their investment strategies to the available spectrum resources (i.e. the regulations of spectrum access).
Keywords: 330; Cost and capacity analysis; Investment Strategies; Licensed and unlicensed spectrum; Outdoor and indoor network deployment; Mobile broadband; Spectrum access; Spectrum authorization schemes